Bioinspired materials for droplet manipulation: Principles, methods and applications. Issue 1 (29th July 2022) - Xu, Jinkai; Xiu, Siyu; Lian, Zhongxu; Yu, Huadong; Cao, Jiaji
Abstract: Droplet manipulation techniques such as transport and merging have been widely used in many fields including biology, chemistry, material and energy applications. Moreover, droplet manipulation strategies have been extensively investigated and reviewed in terms of droplet placement on solid surfaces. However, less attention has been paid to the practice of droplet manipulation technology in other environments, limiting our understanding and the broadening of technology application. In this article, we provided an overview of the recent progress in controlling droplets in various situations, including droplet manipulation on a surface mediated by the passive strategy (Laplace pressure and wettability gradients) and active strategy (electric field, magnetic field, light and heat). We also presented the principle of droplet manipulation and detailed the application of bionic surfaces in droplet manipulation, and the applications and prospects of droplet manipulation technology were summarized. Abstract : This review summarizes the recent progress in the principle, method and application of droplet manipulation on surfaces. Recent methods for droplet manipulation related to bioinspired surfaces with special microstructures and their principles are highlighted. Droplet manipulation using passive and active strategies, their application and future perspectives in related fields are concluded.